Kesalahan Ejaan pada Berita Pendidikan Koran Online Sinar Pagi Edisi Januari 2021 dan Pemanfaatannya sebagai Modul Pembelajaran Menulis Teks Berita - Lena Nurohmah (Universitas Negeri Padang, 2021)
This research was conducted to find out the language errors contained in the Sinar Pagi newspaper news published in January 2021. Sinar Pagi newspaper is a newspaper that has a function to provide information on an event or hottest event that can be opened on the internet. This research began with the discovery of spelling errors in news published on January 30, 2021, for example in writing the word zoom meeting which was not italicized. In fact, the word zoom meeting is an element of a foreign language whose writing must be in italics. The method in this research is qualitative. Data collection techniques using document studies and the method of listening, the instrument is a data card. Based on the results of the analysis found errors in the use of capital letters, writing italics, writing in bold, writing prepositions, writing standard words, writing abbreviations and acronyms, writing affixes, writing compound words, writing particles, writing numbers and numbers, and errors in word usage. connect at the beginning of the sentence. In addition to spelling errors, there were also errors in the use of punctuation marks which included errors in periods, commas, colons, hyphens, slashes, question marks, apostrophes, and the use of spaces, and errors in the use of hyphens at the beginning of sentences. The results of the research will be used as a learning module for News Text Writing in SMP class VIII. Keywords: Language Error, Newspaper, Module